Method for improving BaF2 fluorine ion conductivity based on K doping and grain boundary regulation

Through K doping and grain boundary regulation, a solid electrolyte of BaF2-based fluorine ion battery with a higher room temperature fluorine ion conductivity was designed, which solved the problems of short cycle life of solid fluorine ion batteries and low fluorine ion conductivity, and achieved comprehensive improvement of conductivity and battery performance.

CN119649961AActive Publication Date: 2025-03-18XIANGTAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411699220.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The cycle life of solid fluoride ion batteries is poor, and BaF2 has low fluoride ion conductivity at room temperature, so the mechanical properties and electrochemical windows need to be improved.

Method used

Through K doping and grain boundary regulation, a BaF2-based fluorine ion battery solid electrolyte with a higher room temperature fluorine ion conductivity was designed using first principle and molecular dynamics methods. Specific steps include structural screening, formation energy calculation, fluorine ion conductivity design, energy band structure analysis, mechanical performance calculation and electrochemical window research, and finally determine that the ∑9(221) grain boundary has the highest fluorine ion conductivity.

Benefits of technology

It significantly improves the room temperature fluoride ion conductivity of BaF2, improves its mechanical properties and electrochemical window, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119649961A_ABST
    Figure CN119649961A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving BaF2 fluorinion conductivity based on K doping and grain boundary regulation and control, and mainly provides a technical scheme for solving the problem of low room temperature (300K) fluorinion conductivity of BaF2-based fluorinion solid electrolyte. The method comprises the following steps: firstly, carrying out structure screening on a K-doped BaF2 system (Ba1-xKxF2-x) by adopting a first principle method, calculating and analyzing the relationship between the K concentration (x) and the room-temperature fluorine ion conductivity of the K concentration (x), and designing an optimal K-doped BaF2 crystal (Ba0. 875K0. 125F1.875), the room-temperature fluorine ion conductivity of the optimal K-doped BaF2 crystal being obviously greater than the room-temperature fluorine ion conductivity of BaF2; in addition, the Ba < 0.875 > K < 0.125 > F < 1.875 > has a relatively wide energy band gap, excellent mechanical properties and a relatively wide electrochemical window (0.75 V to 11.48 V); and finally, designing an optimal grain boundary structure (sigma 9 (221)) of Ba0. 875K0. 125F1.875 by adopting a molecular dynamics method, wherein the order of magnitude of the room-temperature fluorine ion conductivity of the optimal grain boundary structure reaches 10 <-3 > S / cm. The invention also provides an effective method for designing the solid electrolyte of the high-performance fluorine ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of computational material chemistry, and specifically relates to a method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation. Background Art

[0002] Solid-state fluoride ion batteries have the advantages of high theoretical voltage, high energy density and good safety performance, and have broad application prospects. However, the current cycle life of solid-state fluoride ion batteries is poor, which seriously restricts its development. How to quickly and accurately develop fluoride ion solid electrolytes with high room temperature (300K) fluoride ion conductivity has become an urgent problem to be solved. In the fluorite-type BaF2 unit cell, Ba ions are cubically densely packed and located at the vertices and face centers of the cubic unit cell; although F ions occupy all tetrahedral voids, they do not occupy octahedral voids, which lays the foundation for the migration of fluoride ions in BaF2; at the same time, due to the strong binding effect of the Ba-F ionic bond on fluoride ions, BaF2 has the problem of low room temperature fluoride ion conductivity, and its mechanical properties and electrochemical window still need to be further improved. Based on this problem, the first-principles method was used to study the mechanism of K-doping regulation of BaF2, and to find the optimal partial replacement of Ba ions by K ions to produce suitable fluorine vacancies and weaken the Ba-F bonding, thereby inducing the rapid diffusion of fluorine ions in BaF2 crystals. The K-doped BaF2 crystal (BaF2) with the highest room temperature fluorine ion conductivity was designed. 0.875 K 0.125 F 1.875 ). In order to further design Ba 0.875 K 0.125 F 1.875 The optimal grain boundary structures of Ba and 0.875 K 0.125 F 1.875 By comparing the fluorine ion conductivity corresponding to the ∑3(111), ∑5(210) and ∑9(221) grain boundaries of Ba 0.875 K 0.125 F 1.875 The ∑9(221) grain boundary has the highest room temperature fluoride ion conductivity (3.68×10 -3 S / cm), which is significantly greater than the fluoride ion conductivity of BaF2. The present invention aims to effectively improve the fluoride ion conductivity of BaF2. Based on the method of K doping and grain boundary regulation, the first principle and molecular dynamics method are used to accurately and quickly design a BaF2-based fluoride ion battery solid electrolyte with high room temperature fluoride ion conductivity. Summary of the invention

[0003] The present invention aims to provide a method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation, aiming to improve its fluoride ion conductivity. The specific implementation method is carried out according to the following steps:

[0004] Step 1: Ba 1-x K x F 2-x (x=0.03125,0.0625,0.09375,0.125,0.15625) for structural screening; then calculate Ba 1-x K x F 2-x The relationship between the formation energy and the K doping concentration (x) is obtained, and the effect of K doping concentration (x) on Ba 1- x K x F 2-x The influence of stability, so as to screen out the optimal K-doping raw material;

[0005] Step 2: Calculate and analyze Ba using the ab initio molecular dynamics (AIMD) method 1-x K x F 2-x The relationship between the fluoride ion conductivity and the K doping concentration (x) at different temperatures was designed. 0.875 K 0.125 F 1.875 , which has the highest fluoride ion conductivity (temperature is 300K);

[0006] Step 3: Calculate Ba using VASP software based on the first principles method 0.875 K 0.125 F 1.875 The band structure of , and analyze its electronic conductivity;

[0007] Step 4: Calculate Ba using VASP software based on the first principles method 0.875 K 0.125 F 1.875 The distribution law of Young's modulus in three-dimensional space is analyzed to analyze its mechanical properties;

[0008] Step 5: Calculate Ba 0.875 K 0.125 F 1.875 The electrochemical window

[0009] Step 6: Build Ba 0.875 K 0.125 F 1.875 The three grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) are studied, and the grain boundary energies of the three are calculated, and the stability of ∑3(111), ∑5(210) and ∑9(221) is compared;

[0010] Step 7: Calculate Ba using LAMMPS software based on molecular dynamics method 0.875 K 0.125 F 1.875 The fluorine ion conductivity of the grain boundaries (∑3(111), ∑5(210) and ∑9(221)) is shown in Table 1. 0.875 K 0.125 F 1.875 The ∑9(221) grain boundary has the highest fluorine ion conductivity (3.68×10 -3 S / cm);

[0011] The present invention proposes a method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation, so as to accurately and quickly design a BaF2-based fluoride ion battery solid electrolyte with high fluoride ion conductivity. 1-x K x F 2-x (x = 0.03125, 0.0625, 0.09375, 0.125, 0.15625) for structural screening; then calculate Ba 1-x K x F 2-x The formation energy under different chemical potentials and different K concentrations is used to determine the Ba with the most stable structure. 1-x K x F 2-x , and obtain the optimal K doping material (K3Ba); then calculate Ba 1-x K x F 2-x The fluoride ion conductivity of (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) was designed to have the highest fluoride ion conductivity. 0.875 K 0.125 F 1.875 ); then calculate and analyze Ba 0.875 K 0.125 F 1.875 The band structure, mechanical properties and electrochemical window of Ba 0.875 K 0.125 F 1.875 The three grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) of the composite were investigated, and the grain boundary energies of the three were calculated to obtain their relative stability. Finally, the LAMMPS software was used to calculate the relative stability of Ba 0.875 K 0.125 F 1.875 The fluorine ion conductivity of the grain boundaries (∑3(111), ∑5(210) and ∑9(221)). The Ba0.875 K 0.125 F 1.875 It not only has a wide energy band gap, excellent mechanical properties and a wide electrochemical window (0.75V-11.48V), but also has the best fluorine ion conductivity (3.68×10 -3 S / cm). BRIEF DESCRIPTION OF THE DRAWINGS

[0012] By describing in detail the embodiments shown in the accompanying drawings, the drawings described below are only some embodiments of the present invention, in which:

[0013] Figure 1 This is an overall flow chart of a method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation;

[0014] Figure 2 (a) The range of relative chemical potential required to form stable BaF2; Figure 2 (b) is Ba 1-x K x F 2-x The formation energy (E) of (x=0.03125,0.0625,0.09375,0.125,0.15625) f (x)) (with K3Ba as doping material);

[0015] Figure 3 (a) is Ba 1-x K x F 2-x Relationship between ln(σT) and K concentration (x) for (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625), where temperature (T) is 300K and σ is Ba 1-x K x F 2-x The fluoride ion conductivity of Figure 3 (b) BaF2 and Ba 0.875 K 0.125 F 1.875 The relationship between ln(σT) and 1000 / T, where σ and T are the fluorine ion conductivity and temperature of the two, respectively, E a represents the activation energy;

[0016] Figure 4 BaF2 and Ba 0.875 K 0.125 F 1.875 The distribution of Young's modulus in three-dimensional space and its projections along the x, y and z directions, in GPa;

[0017] Figure 5(a) When Ba is used as the electrode material of the fluoride ion battery, Ba 0.875 K 0.125 F 1.875 The relationship between the voltage and the amount of Ba reaction; Figure 5 (b) When K is used as the electrode material of the fluoride ion battery, Ba 0.875 K 0.125 F 1.875 The relationship between the voltage and the amount of K reaction;

[0018] Figure 6 For Ba 0.875 K 0.125 F 1.875 Fluoride ion conductivity at grain boundaries (∑3(111), ∑5(210), and ∑9(221)) (temperature 300K); DETAILED DESCRIPTION

[0019] This embodiment provides a method for improving the fluorine ion conductivity of BaF2 based on K doping and grain boundary regulation, comprising the following steps:

[0020] First of all, Ba 1-x K x F 2-x (x=0.03125, 0.0625, 0.09375, 0.125, 0.15625) for structural screening, and then based on the formation of stable Ba 1-x K x F 2-x Required relative chemical potential conditions, calculate its formation energy, compare Ba 1-x K x F 2-x The stability of Ba at different K concentrations was investigated and the optimal K-doped raw material (K3Ba) was obtained. The ab initio molecular dynamics (AIMD) method was then used to calculate the 1-x K x F 2-x The fluoride ion conductivity of (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) was designed, and the Ba with the highest room temperature (300K) fluoride ion conductivity was designed. 0.875 K 0.125 F 1.875 crystal; Ba was then further calculated 0.875 K 0.125 F 1.875 The band structure, mechanical properties and electrochemical window of Ba 0.875 K 0.125 F 1.875The grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) of Ba were designed and their grain boundary energies were calculated to obtain the most stable grain boundary structures. Then, the fluorine ion conductivity of ∑3(111), ∑5(210) and ∑9(221) at different temperatures was calculated and compared. 0.875 K 0.125 F 1.875 The optimal grain boundary (∑9(221)) has the highest fluorine ion conductivity (3.68×10 -3 S / cm). Figure 1 The overall process of a method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation is listed.

[0021] The specific parameters of the first-principles calculation are as follows: the PBE (Perdew-Burke-Ernzerh) method based on the generalized gradient approximation (GGA) is used to deal with the exchange energy, and the projected augmented plane wave (PAW) method is used to describe the interaction between electrons and ions. The plane wave cutoff energy and the Monkhorst-Pack type k-point grid are set to 520 eV and 6×6×6, respectively, and the energy and force convergence accuracy are set to 10 -5 eV / atom and

[0022] First of all, Ba 1-x K x F 2-x (x=0.03125,0.0625,0.09375,0.125,0.15625) to screen the structure, calculate the formation enthalpy of the compounds corresponding to its components, and determine the formation of stable Ba 1-x K x F 2-x The relative chemical potential conditions required for the constituent elements; then calculate Ba according to formula (1-1) 1-x K x F 2-x (x=0.03125, 0.0625, 0.09375, 0.125, 0.15625) under different relative chemical potential conditions (E f (x)), compare Ba 1-x K x F 2-x Stability at different K concentrations and obtaining the optimal K-doped raw material (K3Ba). E f (x) = E tot (Ba 1-x K x F 2-x )-E tot (bulk)+x(ΔμBa +μ Ba )+x(Δμ F +μ F )-x(Δμ K +μ K ) (1-1) In formula (1-1), E tot (Ba 1-x K x F 2-x ) and E tot (bulk) are Ba 1-x K x F 2-x The total energy of and the total energy of BaF2; μ Ba , μ F and μ K are the chemical potentials of Ba, F and K respectively; Δμ Ba , Δμ F and Δμ K are the relative chemical potentials of Ba, F and K respectively. In order to solve Δμ Ba , Δμ F and Δμ K First, the possible competitive phases were searched from the ICSD (Inorganic Crystal Structure Database). Based on the formation enthalpy of the competitive phase, the relative chemical potential (Δμ Ba , Δμ F and Δμ K ) range, the calculation result is as follows Figure 2 (a) is shown. Figure 2 In (a), point A represents the F-rich condition, and point B represents the Ba-rich condition. In order to maintain the stable structure of BaF2 and avoid the formation of other competing phases, Δμ i (i is Ba or F) should satisfy the following constraints (see formula (1-2) - formula (1-3)). Δμ Ba +2Δμ F ≤ΔH f (BaF2) (1-2) Δμ Ba ≤0Δμ F ≤0 (1-3)

[0023] Based on the formation of stable Ba 1-x K x F 2-x Required relative chemical potential (Δμ i) conditions, six K raw materials (KF, KF2, KF3, KF5, K3Ba and KBa3) were considered, and the relative chemical potential constraints of these six compounds were used to calculate the Ba 1-x K x F 2-x The formation energy corresponding to (x=0.03125,0.0625,0.09375,0.125,0.15625) at the boundary points (point A and point B) is compared to show that: Ba 1-x K x F 2-x At point B (Δμ Ba =-11.66eV,Δμ F = 0eV) has a lower formation energy, and its value is negative. The corresponding K raw material is K3Ba, and its formation energy gradually decreases with the increase of K concentration (x) (see Figure 2 (b)), which shows that Ba 1-x K x F 2-x At point B (Δμ Ba =-11.66eV,Δμ F =0eV), and its formation difficulty gradually decreases with the increase of K concentration (x).

[0024] The ab initio molecular dynamics (AIMD) method was used to calculate and analyze the relationship between K concentration (x) and temperature and Ba 1-x K x F 2-x First, we calculate the relationship between the conductivity of fluoride ions in Ba 1-x K x F 2-x The mean square displacement (MSD) in (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) is then derived based on the relationship between the slope of the mean square displacement (MSD) curve and the diffusion coefficient. 1-x K x F 2-x The fluoride ion diffusion coefficients of (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) are calculated. Finally, Ba is calculated based on the fluoride ion diffusion coefficient and the Nernst-Einstein equation. 1-x K x F 2-x Fluoride ion conductivity (σ) of (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625).

[0025] Based on the above method, Ba 1-x K x F2-x (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) fluoride ion conductivity; By comparison, we can know that: Ba 0.875 K 0.125 F 1.875 It has the highest room temperature (300K) fluoride ion conductivity (see Figure 3 (a)).

[0026] According to Ba 0.875 K 0.125 F 1.875 The relationship between the fluoride ion conductivity of BaF2 and temperature is used to deduce the activation energy of the two (the activation energy of BaF2 is listed for comparison only). The calculation results are as follows Figure 3 (b) as shown.

[0027] Ba 0.875 K 0.125 F 1.875 The energy band gap is 6.03 eV, which indicates that it has excellent electronic insulation.

[0028] Calculate Ba based on the relationship between energy and strain 0.875 K 0.125 F 1.875 On this basis, based on the mechanical stability judgment criteria of the tetragonal crystal system, it is further proved that Ba 0.875 K 0.125 F 1.875 Has good mechanical stability.

[0029] According to Ba 0.875 K 0.125 F 1.875 The elastic constants of Ba are used to deduce its bulk modulus (B) and shear modulus (G). Based on the critical B / G value (1.75), Ba 0.875 K 0.125 F 1.875 Whether it is brittle or tough. If the B / G value of the material is greater than 1.75, it indicates that it has good ductility; otherwise, it is brittle. 0.875 K 0.125 F 1.875 The B / G value of Ba is 2.30, which indicates that it has good ductility. 0.875 K 0.125 F 1.875 When used as a solid electrolyte for fluoride ion batteries, it has strong resistance to stress damage during the charge and discharge process.

[0030] Calculate and analyze Ba 0.875 K 0.125 F 1.875The distribution law of Young's modulus (E) of and BaF2 in three-dimensional space (Young's modulus of BaF2 is listed only for comparison), and the projections of the two along the x, y and z directions are obtained. The calculation results are as follows Figure 4 As shown. Figure 4 It can be known: Ba 0.875 K 0.125 F 1.875 The Young's modulus (E) of BaF2 is not only greater than that of BaF2, but also the former is more isotropic than the latter, which indicates that BaF2 0.875 K 0.125 F 1.875 It has better mechanical properties than BaF2, which helps it maintain good cycle stability during the charge and discharge process.

[0031] When Ba and K are used as electrode materials of fluoride ion batteries, calculate Ba 0.875 K 0.125 F 1.875 The electrochemical window of Ba 0.875 K 0.125 F 1.875 The chemical reaction equations corresponding to different voltages obtained the variation law of Ba(K) reaction amount with voltage (such as Figure 5 ). Figure 5 It can be seen that when Ba and K are used as electrode materials, Ba 0.875 K 0.125 F 1.875 The electrochemical windows are 10.73 V and 5.37 V respectively.

[0032] Based on the coincidence lattice theory (CSL), the Ba 0.875 K 0.125 F 1.875 The grain boundary structure (∑3(111), ∑5(210) and ∑9(221)), where ∑ represents the overlap index, which is equal to the ratio of the overlap unit cell volume to the unit cell volume; then calculate Ba according to formula (1-4) 0.875 K 0.125 F 1.875 The grain boundary energy (γ GB ). In formula (1-4), E GB and E bulk Ba 0.875 K 0.125 F 1.875 Grain boundaries (∑3(111), ∑5(210) and ∑9(221)) and Ba 0.875 K0.125 F 1.875 The total energy of the block, A is the grain boundary area. The grain boundary energy (γ GB ) are 0.67 J·m -2 , 0.55 J·m -2 and 0.21 J·m -2 .

[0033] The LAMMPS software was used to analyze the 0.875 K 0.125 F 1.875 Molecular dynamics calculations were performed on the grain boundaries (∑3(111), ∑5(210) and ∑9(221)). First, the mean square displacement (MSD) of fluoride ions in these three grain boundaries was calculated. Then, the fluoride ion diffusion coefficient was derived based on the relationship between the MSD slope and the diffusion coefficient. On this basis, the fluoride ion conductivity (σ) of ∑3(111), ∑5(210) and ∑9(221) was calculated according to the Nernst-Einstein equation.

[0034] Based on the above method, calculate Ba 0.875 K 0.125 F 1.875 The room temperature (300K) fluorine ion conductivity of the grain boundaries (∑3(111), ∑5(210) and ∑9(221)) shows that: Ba 0.875 K 0.125 F 1.875 The ∑9(221) has the highest room temperature (300K) fluoride ion conductivity (3.68×10 -3 S / cm)(See Figure 6 ), which is significantly greater than the room temperature (300K) fluoride ion conductivity of BaF2.

[0035] Finally, it is necessary to explain here that the above-mentioned specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above-mentioned contents of the present invention belong to the protection scope of the present invention.

Claims

1. A method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation, characterized in that: The method comprises the following steps: Step 1: Ba 1-x K x F 2-x (x=0.03125,0.0625,0.09375,0.125,0.15625) for structural screening; then calculate Ba 1-x K x F 2-x The relationship between the formation energy and the K doping concentration (x) is obtained, and the effect of K doping concentration (x) on Ba 1-x K x F 2-x The influence of stability, so as to screen out the optimal K-doping raw material; Step 2: Calculate and analyze Ba using the ab initio molecular dynamics (AIMD) method 1-x K x F 2-x The relationship between the fluoride ion conductivity and the K doping concentration (x) at different temperatures was designed. 0.875 K 0.125 F 1.875 , which has the highest fluoride ion conductivity (temperature is 300K); Step 3: Calculate Ba using VASP software based on the first principles method 0.875 K 0.125 F 1.875 The band structure of , and analyze its electronic conductivity; Step 4: Calculate Ba using VASP software based on the first principles method 0.875 K 0.125 F 1.875 The distribution law of Young's modulus in three-dimensional space is analyzed to analyze its mechanical properties; Step 5: Calculate Ba 0.875 K 0.125 F 1.875 The electrochemical window Step 6: Build Ba 0.875 K 0.125 F 1.875 The three grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) are studied, and the grain boundary energies of the three are calculated, and the stability of ∑3(111), ∑5(210) and ∑9(221) is compared; Step 7: Calculate Ba using LAMMPS software based on molecular dynamics method 0.875 K 0.125 F 1.875 The fluorine ion conductivity of the grain boundaries (∑3(111), ∑5(210) and ∑9(221)) is shown in Table 1. 0.875 K 0.125 F 1.875 The ∑9(221) grain boundary has the highest fluorine ion conductivity (3.68×10 -3 S / cm).

2. The method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 1, Ba 1-x K x F 2-x (x=0.03125,0.0625,0.09375,0.125,0.15625) for structural screening; then calculate Ba 1-x K x F 2-x The relationship between the formation energy and the K doping concentration (x) is obtained, and the effect of K doping concentration (x) on Ba 1-x K x F 2-x The influence of stability is used to screen out the optimal K-doping raw material; the specific steps are as follows: Step 1.1: Calculate the chemical potential (μ) corresponding to each component element of BaF2 i ) and its relative chemical potential (Δμ i ) to obtain the required relative chemical potential region of BaF2. Step 1.2: Calculate and compare the relative chemical potential region of BaF2 required by step 1.1, and compare the relative chemical potential region of BaF2 system (Ba 1- x K x F 2-x ) formation energy, and obtain the effect of K doping concentration (x) on its structural stability. Step 1.3: Compare Ba according to step 1.2 1-x K x F 2-x The formation energies of (x=0.03125, 0.0625, 0.09375, 0.125, 0.15625) screen out K3Ba as the optimal K-doping raw material.

3. The method for improving the fluorine ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 2, the ab initio molecular dynamics (AIMD) method is used to calculate and analyze Ba 1-x K x F 2-x The relationship between the fluoride ion conductivity and the K doping concentration (x) at different temperatures was designed. 0.875 K 0.125 F 1.875 , which has the highest fluoride ion conductivity (temperature is 300K); the specific steps are as follows: Step 2.1: Study the fluoride ion in Ba 1-x K x F 2-x The diffusion process in (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) was studied, and the mean square displacement (MSD) curves under different temperature environments were obtained. Step 2.2: According to the Ba obtained in step 2.1 1-x K x F 2-x The MSD curves under different temperature environments (x=0, 0.03125, 0.0625, 0.09375, 0.125, 0.15625) were used to deduce the fluoride ion conductivity at room temperature (300K).

4. The method for improving the fluorine ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 3, Ba is calculated using VASP software based on the first principle method. 0.875 K 0.125 F 1.875 The band structure of , analyze its electronic conductivity; the specific steps are as follows: Step 3.1: For Ba obtained in step 1 0.875 K 0.125 F 1.875 Static calculations were performed, in which the Brillouin zone k-point grid and cutoff energy based on the Monkhorst-Pack (MP) type were set to 6×6×6 and 520 eV, respectively. Step 3.2: Use the output file obtained in step 3.1 to Ba 0.875 K 0.125 F 1.875 Energy band calculation.

5. The method for improving the fluorine ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 4, VASP software based on the first principle method is used to calculate Ba 0.875 K 0.125 F 1.875 The distribution law of Young's modulus along three-dimensional space is analyzed to analyze its mechanical properties.

6. The method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 5, calculate Ba 0.875 K 0.125 F 1.875 electrochemical window.

7. The method for improving the fluorine ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 6, establish Ba 0.875 K 0.125 F 1.875 The three grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) are studied, the grain boundary energies of these three are calculated, and the stability of ∑3(111), ∑5(210) and ∑9(221) is compared.

8. The method for improving the fluoride ion conductivity of BaF2 based on K doping and grain boundary regulation according to claim 1, characterized in that: In step 7, the LAMMPS software based on the molecular dynamics method is used to calculate Ba 0.875 K 0.125 F 1.875 The fluorine ion conductivity of the grain boundaries (∑3(111), ∑5(210) and ∑9(221)) is shown in Table 1. 0.875 K 0.125 F 1.875 The ∑9(221) grain boundary has the highest fluorine ion conductivity (3.68×10 -3 S / cm); the specific steps are as follows: Step 7.1: Study the fluoride ion in Ba 0.875 K 0.125 F 1.875 The diffusion properties in the grain boundaries (∑3(111), ∑5(210) and ∑9(221)) were investigated, and their MSD curves at different temperatures were obtained. Step 7.2: According to the Ba obtained in step 7.1 0.875 K 0.125 F 1.875 The room temperature (300K) fluoride ion conductivity of the grain boundary structures (∑3(111), ∑5(210) and ∑9(221)) was deduced from the MSD curves under different temperature environments.

Citation Information

Patent Citations

  • Method for calculating anion and cation sites of sulfur-doped lithium titanate

    CN113192577A

  • Design method of novel PrF3-based fluorine ion solid electrolyte

    CN117497097A

  • Method for designing BiOCl chloride ion solid electrolyte based on Mg doping

    CN118062885A

  • Method for improving single-layer Mo2C fluorine ion diffusion performance through vacancy induction

    CN118083980A

  • Method for regulating and controlling LaOCl chlorine storage performance from atomic scale based on Ga doping

    CN118098446A